EFFECT OF CHLORPYRIFOS ON THE DEVELOPMENT OF LUCILIA SERICATA (DIPTERA: CALLIPHORIDAE) - Sisodia, Usha; Lukose, Sally (Journal of Forensic Medicine and Toxicology, 2025)
In entomotoxicology studies, researchers use analytical techniques and equipment to identify chemical compounds in insects that feed down on decaying tissues. Carrion flies consume several substances while feeding on corpses. Insects found on corpses are used to analyze hazardous chemicals qualitatively and quantitatively. Due to these compounds, flies’ cellular physiology can be altered, leading to faster or slower development. Identifying these compounds is crucial for establishing the cause and time of death. The current understanding of pesticides’ effects on blowflies is limited due to a focus on drug detection in entomo-toxicological research. Pesticides, while cost-effective, pose a household hazard and can be used for poisoning at crime scenes. The study examined the influence of chlorpyrifos on the development time and morphology of immature blowflies. Chlorpyrifos is used to kill insects and worms of various plants, but due to its higher use, it has been associated with death from suicide and accidental poisoning. Larvae were reared on pork tissues (muscle and liver) tissues spiked with chlorpyrifos at concentrations found in chlorpyrifos poisoning cases in humans and animals. The untreated pork tissues were considered as a control. The effect of chlorpyrifos concentration on Lucilia sericata was studied under different temperatures (20oC, 25oC, and 30oC). The weight, breadth, and length of L. sericata showed a positive correlation with chlorpyrifos and impacted the development time.